A criticism on strengthening glued laminated timber beams with fibre reinforcement polymers, numerical comparisons between different modelling techniques and strengthening configurations - Çankal, Dilan; Şakar, Gökhan; Kürşat Çelik, Hüseyin (Revista de la Construcción. Journal of Construction, 2023)
The application of CFRP for strengthening timber structures has proven its efficiency in enhancing load-bearing capacity and, in some cases, the stiffness of structural elements, thus providing cost-effective and competitive alternatives both in new design and retrofitting existing historical buildings. In this study, glued laminated timber beams strengthened with CFRP were examined. A number of test beams with different reinforcement configurations and beam sizes were selected from the literature. These beams were analysed with three different methods as numerical, theoretical and code perspective. For the numerical method, a 3D nonlinear finite element model which includes damage and fracture mechanics was constructed. All test beams were studied with different methods and results were compared with respect to initial flexural stiffness, midspan vertical displacement and failure load. The effectiveness of methods and strengthening configurations were stated and suggestions for practical application of FRP-strengthened timber beams were presented.